The Effect of Revolving Funds Policy Implementation on the Productivity of the Cooperative Movement in Medan City - Batubara, Fatimah; Erlina, Erlina; Rujiman, Rujiman (Budapest International Research and Critics University, 2021)
This study aims to determine and describe the implementation of revolving fund assistance policies in cooperatives in the city of Medan. The research objectives are (1) to analyze the effect of revolving funds on increasing cooperative assets, (2) analyzing the effect of revolving funds on increasing cooperative capital, (3) analyzing the effect of revolving funds on increasing cooperative SHU. The main sources of this research are cooperative administrators as implementers and cooperatives that receive aid funds. Data was collected using quantitative descriptive methods, namely by means of observation, interviews and documentation or literature study, namely searching documents related to the research objectives. The technique used is Multiple Regression Analysis. Multiple regression analysis was conducted to examine the effect of two or more independent variables on one dependent variable (Suryani and Hendryadi, 2015). Multiple regression analysis was used to answer research problems through data on revolving funds, assets, capital, and remaining operating results (SHU) on cooperative productivity. The results showed that the revolving fund used by cooperatives in the aspect of assets, capital and SHU had a positive impact. This is indicated by the results of the respondents conducted to 49 cooperative managers representing 8 cooperatives that received revolving funds until March 2021.